2019
DOI: 10.2147/dddt.s193641
|View full text |Cite
|
Sign up to set email alerts
|

<p>Esomeprazole alleviates the damage to stress ulcer in rats through not only its antisecretory effect but its antioxidant effect by inactivating the p38 MAPK and NF-κB signaling pathways</p>

Abstract: BackgroundStress ulcer is a severe complication in critically ill patients and causes a high mortality. The proton pump inhibitor esomeprazole is widely applied in the treatment of stress ulcers because of its powerful acid suppression ability. However, the mechanism of stress ulcer and the precise gastroprotective effect of esomeprazole in stress ulcer remain unclear.PurposeIn the present study, the rats with water-immersed and restraint (WIR)-induced stress ulcer were used to further elucidate the anti-ulcer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
10

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 57 publications
0
12
0
10
Order By: Relevance
“…Therefore, C. vulgaris may improve muscle mass and decrease fat mass through the inactivation of p38 via its antioxidant properties. A previous study reported that esomeprazole, a treatment for stress ulcers, inactivates the p38 MAPK pathway by its antioxidative effect [49].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, C. vulgaris may improve muscle mass and decrease fat mass through the inactivation of p38 via its antioxidant properties. A previous study reported that esomeprazole, a treatment for stress ulcers, inactivates the p38 MAPK pathway by its antioxidative effect [49].…”
Section: Discussionmentioning
confidence: 99%
“…Omeprazole and esomeprazole, the S-isomer of omeprazole, have been reported to have anti-inflammatory effects. Moreover, some studies have reported esomeprazole to inhibit TNF-α and IL-1β and other inflammatory molecules such as IL-6, vascular cell adhesion molecule-1, and inducible nitric oxide synthase, which may contribute to the skin protective effect of omeprazole 17 , 20 , 22 , 23 .…”
Section: Discussionmentioning
confidence: 99%
“…The evaluation of the available studies strongly suggests the involvement of inflammation in the development of capecitabine-induced HFS 16 . On the other hand, proton pump inhibitors (PPIs), including omeprazole, are reported to have anti-inflammatory effects in several animal models 17 21 . We hypothesized that omeprazole, with its anti-inflammatory properties, may be effective in preventing or treating HFS.…”
Section: Introductionmentioning
confidence: 99%
“…Esomeprazole has also shown to have a gastro-protective role via its antioxidant activity through inhibiting the signalling pathway of NF-B and p38 MAPK. Treatment with esomeprazole also led to increased antioxidant factors expressions such as GSH and SOD and decreased MDA levels and other invasive triggers such as pepsin, gastric acid and ROS-related inflammatory damage 26 .…”
Section: Proton Pump Inhibitors and Antioxidant Potentialmentioning
confidence: 94%